Influence of Genotype, Environment, and Crop Management on the Yield and Bread-Making Quality in Spring Wheat Cultivars - Abu Zar Ghafoor; Alicja Ceglińska; Hassan Karim; Magdalena Wijata; Grzegorz Sobczyński; Adriana Derejko; Marcin Studnicki; Jan Rozbicki; Grażyna Cacak-Pietrzak (Agriculture)
Obtaining optimal wheat cultivars that balance high productivity and grain processing quality in diverse environmental and crop management conditions requires a comprehensive assessment of the influence of genetic and environmental factors and their interactions. This study investigated the influence of these factors on yield, grain quality, and bread-making traits in spring wheat (Triticum aestivum L.) cultivars. The study was conducted at four trial locations in the temperate climate area over two consecutive growing seasons, each with two different crop management approaches (moderate and high input). We observed a strong influence of genotype on grain quality (e.g., protein content, test weight) and farinographic in spring wheat. Environmental factors strongly influenced the variability of dough softening and quality number among the studied rheological traits. However, we observed that crop management significantly impacted dough stability. The strength of the relationships between yield, grain quality, and bread-making traits depended on the specific crop management used. The multi-trait stability of genotypes in yield, grain quality, and bread-making traits also varied, depending on the crop management method.